2001
DOI: 10.1046/j.1524-475x.2001.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a cell‐based interactive wound dressing to enhance healing of excisional wounds in nude mice

Abstract: The need to have viable, metabolically active cells to heal wounds is well recognized, because there is clear evidence that cellular dysfunction delays healing. This suggests that addition of metabolically active cells to a delayed healing tissue could enhance the healing of the tissue. Therefore, we examined the ability of an interactive wound dressing composed of human keratinocytes or fibroblasts grown on microporous bio-reactor beads and placed into a polyethylene bag to facilitate the delayed healing of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
3
7
0
Order By: Relevance
“…As such, we did not perform bacterial culture study. Our experience is very much in line with many previous wound studies in which nude mice were successfully used for various wound studies [32][33][34]. Second, this model mimics the acute wound healing process in healthy animals.…”
Section: Commentssupporting
confidence: 76%
“…As such, we did not perform bacterial culture study. Our experience is very much in line with many previous wound studies in which nude mice were successfully used for various wound studies [32][33][34]. Second, this model mimics the acute wound healing process in healthy animals.…”
Section: Commentssupporting
confidence: 76%
“…To our knowledge, this study presents for the first time a comprehensive data set comparing microcarrier‐bioreactor culture with 2D monolayer culture for the in vitro expansion of human epidermal keratinocytes. Whilst our results support previous studies15–18, 21, 22 that keratinocytes can be expanded on microcarriers without the use of murine feeder cells, this is the first study to use microcarrier keratinocyte expansion without prior subcultivation via 2D‐culture.…”
Section: Discussionsupporting
confidence: 90%
“…Microcarriers have a considerably larger surface to volume ratio compared to standard two‐dimensional (2D) culture for the keratinocytes to proliferate15, 18–20 and this surface area can be further enlarged by the use of macroporous microcarriers 19. Indeed, clinical13, 17, 21 and animal14, 16, 18, 22 studies using microcarrier‐expanded keratinocytes have demonstrated promising results in the treatment of skin defects. However, these clinical investigations failed to quantify cell proliferation and demonstrate the expression of epidermal markers during keratinocyte expansion on microcarriers 13, 17, 21.…”
Section: Introductionmentioning
confidence: 99%
“…We chose nude mice to study the function of ATP7A in macrophages in vivo because these T-cell-deficient mice are widely used to investigate the function of transplanted human cells, particularly genetically modified cells, in dermal wounds [25] and cancer. Moreover, macrophage distribution and density are not significantly altered between nude and control mice after a wound [26], indicating that nude mice can replicate the physiological behavior of macrophages.…”
Section: Discussionmentioning
confidence: 99%